Antimicrobial use for the management of varicella in Thailand: a retrospective observational study - Chokephaibulkit K. (2023)
Objective: To describe the clinical characteristics of varicella patients seeking medical consultation and the use of antimicrobials for their management in Thailand in the absence of universal varicella vaccination (UVV). Methods: A multicenter, retrospective chart review of 260 children and adults with a primary diagnosis of varicella was conducted at one private and three public hospitals in Bangkok, Thailand. Charts of varicella patients (inpatient or outpatient) were randomly selected over a 5-year period. Key outcomes included clinical complications and the use of antibiotics, antivirals, and other medications. Results: Charts of 200 children (mean age 5.7 years, range 0.3–16 years) and 60 adults (mean age 27.9 years, range 18–50 years) were reviewed. Fourteen patients (including 8 children) were hospitalized. Five percent of the children and none of the adults were immunocompromised. At least 1 varicella-related complication was reported by 7.3% (7% of children, 8.3% of adults, p =.778) of all patients, including 57.1% (62.5% of children, 50% of adults) of inpatients (p <.001, compared with outpatients). Skin/soft tissue infection (47.7%) and dehydration (47.4%) were the most common complications. Antivirals (mainly oral acyclovir) were prescribed to 46.5% of patients (31.5% of children, 96.7% of adults, p <.001). Antibiotics were prescribed to 20.8% of patients (19% of children, 26.7% of adults, p =.199). Topical, oral, and intravenous antibiotics were prescribed to 12.3%, 8.5%, and 1.2% of patients, respectively. Antimicrobial prescriptions were higher among adults (p <.001) and immunocompromised patients (p =.025). Apart from antimicrobials, acetaminophen (62.3%) and oral antihistamines (51.5%) were the most prescribed. Conclusion: A considerable number of varicella patients, both children and adults, seeking medical consultation in Thai hospitals are prescribed antibiotics and antivirals, with one-fifth of patients being prescribed an antibiotic and almost half prescribed an antiviral. The study may be of interest to policymakers in Thailand and other Asia-Pacific countries considering UVV implementation.